2001
DOI: 10.1007/s11886-001-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for acute coronary syndromes and percutaneous coronary intervention in patients with heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is not uncommon in clinical practice, and may go unrecognized in a substantial number of patients. The pathophysiology of HIT has only recently been better understood. Patients with HIT may require anticoagulation for thrombotic complications that result in severe morbidity and mortality. These patients may also require anticoagulation for acute coronary syndromes (ACS), or during percutaneous coronary interventions (PCIs). The direct thrombin inhibitors are currently the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Minor bleeding complications, usually at the site of a prior vascular puncture, occurred in nine patients (23%). 28,38,39 Clinical outcomes were comparable to historical data sets overall.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 74%
See 2 more Smart Citations
“…Minor bleeding complications, usually at the site of a prior vascular puncture, occurred in nine patients (23%). 28,38,39 Clinical outcomes were comparable to historical data sets overall.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 74%
“…Bivalirudin has been studied prospectively for use during PCI in patients with acute or previous HIT. 28,38,39 Efficacy and safety of bivalirudin from two studies that included 39 patients who required alternative anticoagulation have been reported. 28,38 Among 39 patients whom received bivalirudin, 17 had active HIT or HITTS and 22 had a history of HIT.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice thrombocytopenia (platelet count < 100 x 10 3 /mm 3 ) is more common than may be recognized. 20 Type II HIT occurs in 1-3% of patients treated with heparin, and it can be lifethreatening in some patients. 20 Although thrombocytopenia most often is associated with heparin, it has been reported with LMWH, glycoprotein IIb/IIIa inhibitors, and the thienopyridines.…”
Section: Clinical Concerns: Patients With Acute Coronary Syndromes Anmentioning
confidence: 99%
“…20 Type II HIT occurs in 1-3% of patients treated with heparin, and it can be lifethreatening in some patients. 20 Although thrombocytopenia most often is associated with heparin, it has been reported with LMWH, glycoprotein IIb/IIIa inhibitors, and the thienopyridines. 21 In contrast, bivalirudin does not cross-react with HIT antibodies.…”
Section: Clinical Concerns: Patients With Acute Coronary Syndromes Anmentioning
confidence: 99%